Preparation method of vanadium titano-magnetite oxidized pellets
By mixing and grinding the sulfuric acid slag with quicklime and mixing it with vanadium titanium magnetite, the problems of difficulty in oxidation and low compressive strength of vanadium titanium magnetite slag are solved, the quality of the pellets and blast furnace smelting performance are improved, and the efficient utilization of sulfuric acid slag is achieved.
Patent Information
- Application Number
- CN202411893850.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-18
AI Technical Summary
Vanadium titanium magnetite pellets have difficulty oxidizing during the roasting process, low compressive strength, and poor spherical properties of sulfuric acid slag, which affects the quality of the pellets and blast furnace smelting performance.
By mixing and grinding the solid waste resource sulfuric acid slag with quicklime, forming a first mixture and mixing it with vanadium titanium magnet concentrate and binder, a slag slag vanadium titanium magnetite oxidation pellet is prepared. This method improves the utilization rate of sulfuric acid residue and the compressive strength of the pellets.
It improves the utilization rate of sulfuric acid slag, alleviates the accumulation of sulfuric acid slag and environmental pollution, enhances the compressive strength and metallurgical properties of vanadium titanium magnetite pellets, and reduces the cost of iron smelting.
Smart Images

Figure CN119640028A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metallurgy, and in particular to a method for preparing vanadium-titanium magnetite oxide pellets. Background Art
[0002] Vanadium-titanium magnetite has close coexistence of iron and titanium, and cannot be effectively separated during the beneficiation process. Most of the titanium exists in the form of ilmenite crystals. After being sorted and upgraded, it enters the concentrate together with iron to form a vanadium-titanium magnetite concentrate, whose TFe grade is relatively low at about 56%, and the TiO2 content is as high as more than 10%. As an important raw material for blast furnace smelting of vanadium-titanium ore, the vanadium-titanium magnetite pellets have high TiO2, MgO, Al2O3 and S contents, fine particle size and large surface area. Compared with ordinary pellets, the internal oxidation of the pellets is difficult, the oxidation preheating time is longer, the controllable temperature range of the pellet roasting is narrow, and the pellet production process is complex. During the pellet roasting process, Fe2O3 and TiO2 will generate ironbrookite, which is embedded between magnetite grains, hindering the connection between hematite grains and affecting the growth and connection of hematite grains. The compressive strength of vanadium-titanium ore pellets is only about 2200N / piece, which is much lower than the strength of ordinary pellets of about 3000N / piece. In addition, the TFe grade of vanadium-titanium magnetite pellets is low, generally around 55%.
[0003] Sulfuric acid slag is the roasting slag in the production process of preparing sulfuric acid from pyrite. It is an inevitable product of acid-making chemical plants. At present, a large amount of sulphuric acid slag is connected all over the country. The rich secondary mineral resources have not been fully and effectively utilized, which not only occupies land resources, but also poses the risk of environmental pollution. Sulfuric acid slag is mainly composed of calcium sulfate, iron oxides, silicates and other components. After a series of sorting and quality improvement, the TFe grade can reach about 60%. The iron oxides are mainly magnetite and hematite. Sulfuric acid slag has fine particle size and large specific surface area. It can be used as an adhesive powder in the process of material balling; it has rich microscopic pore structure and strong water absorption. The moisture content of the raw ball of the whole sulphuric acid slag pellet can reach 23%, which is far higher than the 7~9% of the raw ball of ordinary pellet ore. Excessive moisture content is not conducive to the drying of the pellets. Based on the above characteristics, sulphuric acid slag is often added to the mixture of iron ore concentrate and binder in a small amount for pellet production.
[0004] Since the crystal form of sulfate slag grows well after roasting, less primary crystal is formed under high temperature conditions when producing oxidized pellets, and the bridge bond consolidation effect is weak, which affects the compressive strength of the pellets. The oxidized pellets of sulfate slag can be strengthened by improving the crystal defects of sulfate slag and improving the spheroidization of sulfate slag. Common methods include adding high-pressure roller mills. For example, Chinese patent No. CN101643842A discloses a method for strengthening the direct production of oxidized pellets using sulfate slag.
[0005] The addition of sulfuric acid slag to vanadium-titanium magnetite pellets is beneficial to improving the TFe grade of the raw material entering the blast furnace, but the poor ball-forming property and weak high-temperature consolidation effect of sulfuric acid slag will affect the compressive strength of the vanadium-titanium magnetite pellets. Therefore, it is necessary to optimize technical methods to improve the quality of vanadium-titanium magnetite pellets added with sulfuric acid slag.
[0006] In view of this, improvements should be proposed to the prior art to solve the above-mentioned problems existing in the prior art. Summary of the invention
[0007] The main purpose of the present invention is to provide a method for preparing vanadium-titanium magnetite oxide pellets, in which solid waste resource sulfuric acid slag is added to the vanadium-titanium magnetite pellet raw material to prepare sulfuric acid slag vanadium-titanium magnetite oxide pellets, thereby improving the utilization rate of sulfuric acid slag, which is beneficial to alleviating the problems of sulfuric acid slag accumulation occupying land and environmental pollution. For vanadium-titanium magnetite pellets, adding sulfuric acid slag can improve the TFe grade of the pellets, which is beneficial to improving the grade of blast furnace smelting and reducing ironmaking costs.
[0008] According to one aspect of the present invention, a method for preparing vanadium-titanium magnetite oxide pellets is provided, which comprises the following steps: S1. By weight, 0.5-1.5 parts of quicklime and 2-5 parts of slag sulfate are mixed and ground to obtain a first mixture, and 93-96 parts of vanadium-titanium magnetite concentrate, 1-2 parts of a binder and the first mixture are mixed to obtain a second mixture; S2, pelletizing the second mixed material in a disc pelletizing machine to obtain green pellets; S3, drying, preheating, roasting and cooling the green balls obtained in step S2 to obtain sulfate slag vanadium-titanium magnetite oxide balls.
[0009] According to one embodiment of the present invention, the CaO content in quicklime is 80-98%, and the grade of sulfate slag TFe is 58-62%.
[0010] According to one embodiment of the present invention, the proportion of particle size <0.074 mm in the sulfate slag is 96-98%.
[0011] According to one embodiment of the present invention, the TFe grade of the vanadium-titanium magnetite concentrate is 53-56%, and the proportion of the particle size <0.074 mm is 90-98%.
[0012] According to one embodiment of the present invention, the binder is bentonite.
[0013] According to one embodiment of the present invention, the pelletizing time is 15 to 20 minutes.
[0014] According to one embodiment of the present invention, the moisture content of the raw balls is controlled to be 7-8.5%.
[0015] According to one embodiment of the present invention, the particle size of the green balls is controlled to be 10-12.5 mm.
[0016] According to one embodiment of the present invention, the mixing and grinding time of quicklime and sulfuric acid slag is 20 to 40 minutes.
[0017] According to one embodiment of the present invention, in step S3, the drying temperature ranges from 100 to 115°C, the preheating temperature ranges from 900 to 1000°C, and the calcining temperature ranges from 1230 to 1260°C.
[0018] In a method for preparing vanadium-titanium magnetite oxide pellets according to an embodiment of the present invention, solid waste resource sulphuric acid slag is added to the vanadium-titanium magnetite pellet raw material to prepare sulphuric acid slag vanadium-titanium magnetite oxide pellets, which improves the utilization rate of sulphuric acid slag, helps to alleviate the problem of sulphuric acid slag accumulation occupying land and environmental pollution. For vanadium-titanium magnetite pellets, adding sulphuric acid slag can improve the TFe grade of the pellets, which is beneficial to improve the grade of blast furnace smelting and reduce ironmaking costs. At the same time, sulphuric acid slag as a solid waste resource can reduce the raw material cost of pellets. Sulphuric acid slag has poor balling performance, few crystal defects, and poor high-temperature continuous crystal consolidation. By pre-grinding sulphuric acid slag and quicklime, due to the difference in hardness of the two substances, the difference in local stress during the grinding process can promote more friction and collision between crystal particles, making it easier to produce fractures and defects. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] In order to more clearly illustrate the technical solution of the embodiment of the present invention, the drawings required for use in the embodiment will be briefly introduced below. Obviously, the drawings described below are only some implementation cases of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0020] Figure 1 The process flow chart of the method for preparing vanadium-titanium magnetite oxide pellets according to the present invention is shown. DETAILED DESCRIPTION
[0021] The detailed description of the following embodiments is used to exemplify the principles of the present invention, but cannot be used to limit the scope of the present invention. The present invention can be implemented in many different forms and is not limited to the specific embodiments disclosed herein, but includes all technical solutions falling within the scope of the claims.
[0022] The present invention provides these embodiments to make this disclosure thorough and complete, and fully express the scope of the present invention to those skilled in the art. It should be noted that unless otherwise specifically stated, the relative arrangement of the parts and steps, the composition of materials, numerical expressions and numerical values set forth in these embodiments should be interpreted as being merely exemplary, rather than as limiting.
[0023] It should be noted that, in the description of the present invention, unless otherwise specified, the meaning of "multiple" is greater than or equal to two; the terms "upper", "lower", "left", "right", "inner", "outer", etc., indicating the orientation or positional relationship, are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present invention. When the absolute position of the object being described changes, the relative positional relationship may also change accordingly.
[0024] It should also be noted that in the description of the present invention, unless otherwise clearly specified and limited, the terms "installed", "connected" and "connected" should be understood in a broad sense. For example, it can be a fixed connection, a detachable connection, or an integral connection; it can be directly connected or indirectly connected through an intermediate medium. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to the specific circumstances. When a specific device is described as being located between a first device and a second device, there may or may not be an intermediate device between the specific device and the first device or the second device.
[0025] All terms used in the present invention have the same meanings as those understood by those of ordinary skill in the art to which the present disclosure belongs, unless otherwise specifically defined. It should also be understood that terms defined in general dictionaries, for example, should be interpreted as having meanings consistent with their meanings in the context of the relevant technology, and should not be interpreted in an idealized or extremely formal sense, unless explicitly defined herein.
[0026] Technologies, methods, and apparatus known to ordinary technicians in the relevant art may not be discussed in detail, but where appropriate, these technologies, methods, and apparatus should be considered part of the specification.
[0027] like Figure 1 As shown, the present invention provides a method for preparing vanadium-titanium magnetite oxide pellets, which comprises the following steps: S1. By weight, 0.5-1.5 parts of quicklime and 2-5 parts of slag sulfate are mixed and ground to obtain a first mixture, and 93-96 parts of vanadium-titanium magnetite concentrate, 1-2 parts of a binder and the first mixture are mixed to obtain a second mixture; S2, pelletizing the second mixed material in a disc pelletizing machine to obtain green pellets; S3, drying, preheating, roasting and cooling the green balls obtained in step S2 to obtain sulfate slag vanadium-titanium magnetite oxide balls.
[0028] The addition of sulfuric acid slag improves the TFe grade of vanadium-titanium magnetite pellets. The compressive strength of the finished pellets is higher than that of ordinary vanadium-titanium magnetite pellets. At the same time, it has good metallurgical properties and meets the production needs of blast furnaces. In terms of production, the addition of sulfuric acid slag and quicklime can reduce the cost of pellet raw materials and ironmaking costs.
[0029] The quality of the finished pellets can be effectively improved by premixing and grinding sulfate slag and quicklime to produce vanadium-titanium magnetite pellets. The finished vanadium-titanium magnetite oxide pellets produced by this method have improved compressive strength, improved TFe grade, good metallurgical properties, and have application and promotion value.
[0030] In some specific embodiments, the CaO content in quicklime is 80-98%, and the TFe grade of sulfate slag is 58-62%.
[0031] In some specific embodiments, the particle size of <0.074 mm in the sulfate slag accounts for 96-98%.
[0032] In some specific embodiments, the amount of quicklime added is 1 to 3 parts by weight.
[0033] In some specific embodiments, the TFe grade of the vanadium-titanium magnetite concentrate is 53-56%, and the particle size <0.074 mm accounts for 90-98%.
[0034] In some specific embodiments, the binder is bentonite. Bentonite has good adhesion and plasticity, and can effectively bond the raw material particles together to form a solid pellet. This high-strength pellet can remain intact in the subsequent smelting process, reduce pulverization, and improve production efficiency. Bentonite forms a mesh structure inside the pellet, which helps to improve the air permeability of the pellet. Good air permeability is crucial for the reduction reaction of the pellet during the smelting process. It can promote the diffusion of gas inside the pellet, increase the reduction rate and reduction degree, and thus improve the quality of the pellet.
[0035] In some specific embodiments, the pelletizing time is 15 to 20 minutes.
[0036] Based on the above embodiments, the moisture content of the raw balls is controlled to be 7-8.5%.
[0037] Based on the above embodiments, the particle size of the raw balls is controlled to be 10-12.5 mm.
[0038] Based on the above embodiment, the mixing and grinding time of quicklime and sulfuric acid slag is 20 to 40 minutes. Preferably, the mixing and grinding time is 30 minutes.
[0039] On the basis of the above embodiment, in step S3, the drying temperature ranges from 100 to 115°C, the preheating temperature ranges from 900 to 1000°C, and the calcining temperature ranges from 1230 to 1260°C.
[0040] The present application is described below through specific examples and comparative examples.
[0041] Comparative Example 1 A method for preparing vanadium-titanium magnetite oxide pellets comprises the following steps: S1. Mix dried vanadium-titanium magnetite concentrate powder and bentonite to obtain a first mixed ore powder, wherein the magnetite concentrate raw material accounts for 98% by mass, and the bentonite raw material accounts for 2% by mass.
[0042] S2. The first mixed mineral powder 1 of step S1 is pelletized in a disc pelletizer. The pelletizing time is 20 minutes. The moisture content of the raw balls is 7.51% and the particle size is 10-12.5 mm.
[0043] The performance test of the green ball is as follows: the green ball falls 3 times / piece, the compressive strength of the green ball is 11.35N / piece, and the bursting temperature is >600℃.
[0044] S3. After drying the green balls obtained in step S2, preheating them at 950° C. for 20 min, roasting them at 1250° C. for 12 min, and obtaining vanadium-titanium magnetite oxide balls after cooling.
[0045] The compressive strength test result of the vanadium-titanium magnetite oxide pellets prepared in Comparative Example 1 is 2378N / piece.
[0046] Comparative Example 2 A method for preparing vanadium-titanium magnetite oxide pellets comprises the following steps: S1. Take dry vanadium-titanium magnetite concentrate powder, sulfuric acid slag and bentonite and mix them to obtain the first mixed ore powder, wherein the mass proportion of the vanadium-titanium magnetite concentrate raw material is 96%, the mass proportion of the sulfuric acid slag raw material is 2%, and the mass proportion of the bentonite raw material is 2%.
[0047] S2. The first mixed mineral powder in step S1 is pelletized in a disc pelletizer. The pelletizing time is 20 minutes, the moisture content of the raw balls is 8.34%, and the particle size of the raw balls is 10-12.5 mm.
[0048] The performance test of the green ball is as follows: the green ball falls 2.2 times / piece, the green ball compressive strength is 8.37N / piece, and the bursting temperature is >600℃.
[0049] S3. After drying the green balls obtained in step S2, preheating them at 950° C. for 20 min, roasting them at 1250° C. for 12 min, and obtaining vanadium-titanium magnetite oxide balls after cooling.
[0050] The compressive strength test result of the vanadium-titanium magnetite oxide pellets prepared in Comparative Example 2 is 2286N / piece.
[0051] Example 1 A method for preparing vanadium-titanium magnetite oxide pellets comprises the following steps: S1. Mix and grind dried sulphuric acid slag and quicklime to obtain a first mixed ore powder, the grinding time is 30 min, the sulphuric acid slag raw material accounts for 2% by mass, and the quicklime raw material accounts for 0.5% by mass; mix dried vanadium-titanium magnetite concentrate powder, the first mixed ore powder and bentonite to obtain a second mixed ore powder, the vanadium-titanium magnetite concentrate raw material accounts for 96% by mass, and the bentonite raw material accounts for 1.5% by mass.
[0052] S2. The second mixed mineral powder of step S1 is pelletized in a disc pelletizer. The pelletizing time is 20 minutes, the moisture content of the raw balls is 8.01%, and the particle size of the raw balls is 10-12.5 mm.
[0053] The performance test of the green ball is as follows: the green ball falls 3.4 times / piece, the green ball compressive strength is 11.14N / piece, and the bursting temperature is >600℃.
[0054] S3. After drying the green pellets obtained in step S2, preheat them at 950° C. for 20 min, roast them at 1250° C. for 12 min, and obtain sulfate slag oxidation pellets after cooling.
[0055] The compressive strength test result of the sulfate slag oxidation pellets prepared in Example 1 is 2637N / piece.
[0056] This application conducts performance testing on pellets based on standards GB / T14201-2018 "Determination of compressive strength of iron pellets for blast furnace and direct reduction" and GB / T27692-2011 "Acidic iron pellets for blast furnace".
[0057] Table 1 shows the preparation and quality parameter comparison of vanadium-titanium magnetite oxidized pellets. Due to the strong water absorption of sulfuric acid slag, the moisture content of vanadium-titanium magnetite pellets increases after adding sulfuric acid slag, the falling strength and compressive strength of green balls decrease, and the compressive strength of cooked balls decreases. When vanadium-titanium magnetite is prepared by the method of pre-mixing and grinding "sulfuric acid slag + quicklime", the falling strength of green balls increases, the compressive strength of green balls remains basically unchanged, and the compressive strength of cooked balls is significantly improved. Table 2 shows the chemical composition of vanadium-titanium magnetite oxidized pellets. It can be seen that the TFe grade of vanadium-titanium magnetite pellets increases after adding sulfuric acid slag.
[0058] Table 1 Parameters of Example of Vanadium Titanium Magnetite Oxidation Pellets
[0059] Table 2 Chemical composition of vanadium-titanium magnetite oxide pellets
[0060] The method for preparing vanadium-titanium magnetite oxide pellets proposed in the present invention adds solid waste resource sulfuric acid slag to the vanadium-titanium magnetite pellet raw material to prepare sulfuric acid slag vanadium-titanium magnetite oxide pellets, which improves the utilization rate of sulfuric acid slag and is beneficial to alleviating the problem of sulfuric acid slag accumulation occupying land and environmental pollution.
[0061] For vanadium-titanium magnetite pellets, adding sulfuric acid slag can improve the TFe grade of the pellets, which is beneficial to improve the grade of blast furnace smelting and reduce the cost of ironmaking. At the same time, sulfuric acid slag as a solid waste resource can reduce the raw material cost of pellets. Sulfate slag has poor ball-forming performance, few crystal defects, and poor high-temperature crystal consolidation. By pre-grinding sulfuric acid slag and quicklime, due to the difference in hardness of the two materials, the difference in local stress during the grinding process can promote more friction and collision between crystal particles, making it more likely to produce fractures and defects.
[0062] The high activity of CaO can promote crystal interface reactions and form new chemical bonds or defects. 2+ It can be doped into the sulfate slag crystal as an impurity ion to cause instability and increase of defects in the crystal structure. Compared with the conventional pellet preparation method, the pre-grinding not only fully mixes the two raw materials, improves the mixing uniformity of the pelletizing raw materials, but also improves the high-temperature reaction activity of the raw materials. The CaO in the quicklime of the present invention can also play a bonding role in the pelletizing process, which is beneficial to reduce the amount of the binder bentonite and reduce the cost of raw materials.
[0063] The quality of the finished pellets can be effectively improved by premixing and grinding sulfate slag and quicklime to produce vanadium-titanium magnetite pellets. The finished vanadium-titanium magnetite oxide pellets produced by this method have improved compressive strength, improved TFe grade, good metallurgical properties, and have application and promotion value.
[0064] The above are exemplary embodiments disclosed in the present invention. The order disclosed in the above embodiments of the present invention is for description only and does not represent the advantages and disadvantages of the embodiments. However, it should be noted that the discussion of any of the above embodiments is only exemplary and is not intended to imply that the scope disclosed in the embodiments of the present invention (including the claims) is limited to these examples. Various changes and modifications may be made without departing from the scope defined in the claims. The functions, steps and / or actions of the method claims according to the disclosed embodiments described herein do not need to be performed in any particular order. In addition, although the elements disclosed in the embodiments of the present invention may be described or required in individual form, they may also be understood as multiple unless explicitly limited to the singular.
[0065] A person skilled in the art should understand that the discussion of any of the above embodiments is only exemplary and is not intended to imply that the scope of the disclosure of the embodiments of the present invention (including the claims) is limited to these examples; under the concept of the embodiments of the present invention, the technical features in the above embodiments or different embodiments can also be combined, and there are many other changes in different aspects of the embodiments of the present invention as described above, which are not provided in detail for the sake of simplicity. Therefore, any omissions, modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the embodiments of the present invention should be included in the protection scope of the embodiments of the present invention.
Claims
1. A method for preparing vanadium-titanium magnetite oxide pellets, characterized in that: The following steps are involved: S1. By weight, 0.5-1.5 parts of quicklime and 2-5 parts of slag sulfate are mixed and ground to obtain a first mixture, and 93-96 parts of vanadium-titanium magnetite concentrate, 1-2 parts of a binder and the first mixture are mixed to obtain a second mixture; S2, pelletizing the second mixed material in a disc pelletizing machine to obtain green pellets; S3, drying, preheating, roasting and cooling the green balls obtained in step S2 to obtain sulfate slag vanadium-titanium magnetite oxide balls.
2. The method for preparing vanadium-titanium magnetite oxide pellets according to claim 1, characterized in that: The CaO content in the quicklime is 80-98%, and the TFe grade of the sulfate slag is 58-62%.
3. The method for preparing vanadium-titanium magnetite oxide pellets according to claim 1, characterized in that: The particle size of <0.074 mm accounts for 96-98% of the sulfate slag.
4. The method for preparing vanadium-titanium magnetite oxide pellets according to claim 1, characterized in that: The TFe grade of the vanadium-titanium magnetite concentrate is 53-56%, and the proportion of the particle size <0.074 mm is 90-98%.
5. The method for preparing vanadium-titanium magnetite oxide pellets according to claim 1, characterized in that: The binder is bentonite.
6. The method for preparing vanadium-titanium magnetite oxide pellets according to claim 1, characterized in that: The pelletizing time is 15 to 20 minutes.
7. The method for preparing vanadium-titanium magnetite oxide pellets according to claim 1, characterized in that: The moisture content of the raw balls is controlled to be 7-8.5%.
8. The method for preparing vanadium-titanium magnetite oxide pellets according to claim 1, characterized in that: The particle size of the raw balls is controlled to be 10-12.5 mm.
9. The method for preparing vanadium-titanium magnetite oxide pellets according to claim 1, characterized in that: The mixing and grinding time of the quicklime and the sulfuric acid slag is 20 to 40 minutes.
10. The method for preparing vanadium-titanium magnetite oxide pellets according to claim 1, characterized in that: In step S3, the drying temperature ranges from 100 to 115°C, the preheating temperature ranges from 900 to 1000°C, and the calcining temperature ranges from 1230 to 1260°C.
Citation Information
Patent Citations
Method for strengthening oxidized pellet prepared by directly using sulfate slag
CN101643842A
Technique for producing agglomeration by mixing sulfuric acid residue and concentrate
CN101260460A
Method for preparing high strength green pellets from steel plant iron-containing dust
CN102618718A
Method for producing alkaline pellets by using neutralization slag and sulfuric acid slag
CN112813258A
Multifunctional additive for strengthening high-FeO spinel type iron ore concentrate oxidation and pellet roasting consolidation
CN115572817A